Las Derechas : the extreme right in Argentina, Brazil, and Chile, 1890-1939 - Deutsch, Sandra McGee 1950- (Stanford University Press, 1999)
"This is the first book to explicitly compare extreme rightist organizations, ideas, and actions in different national settings in Latin America. Hardly an undifferentiated whole, the right in Argentina, Brazil, and Chile has changed over time and has contained moderate and extreme factions: the book's title, Las Derechas, emphasizes this diversity. The author focuses on extreme right-wing movements, showing how their class and gender composition, motives, programs, and activities varied over time and between countries."--Jacket